Religious pluralism in theoretical perspective: Exploring concepts, relevance, and challenges in Religious Studies - Malik, Nida Husna Abdul; Huriani, Yeni; Waluyajati, Roro Sri Rejeki; Kustana, Kustana (FISIP UIN SGD Bandung, 2025)
This article critically examines the concept of pluralism within the study of religion, addressing both its theoretical foundations and practical applications across various countries. Religious pluralism is understood as the recognition of religious diversity as a social and theological reality that must be approached with openness, dialogue, and mutual respect. Employing a qualitative approach through literature review, this study analyzes key works by Paul F. Knitter, Wilfred Cantwell Smith, and Alwi Shihab, while also presenting case studies from Indonesia, India, the United States, and Western Europe. The findings reveal that pluralism is not merely a moral ideal but also a necessary framework for promoting peaceful coexistence amid difference. Despite facing challenges such as fundamentalism, discrimination, and identity politics, pluralism remains relevant as a foundation for inclusive and transformative religious studies. The article recommends strengthening interfaith education, supporting diversity-oriented policies, and encouraging religious leaders to foster interreligious dialogue. Contribution: The study offers actionable recommendations aimed at enhancing interfaith education, supporting policies that encourage diversity, and promoting interreligious dialogue, thereby enriching both academic discourse and practical efforts toward inclusive and transformative religious engagement.